2008
DOI: 10.31901/24566772.2008/02.02.10
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Iron Supplementation on Anemia During Pregnancy

Abstract: Patients seek cures from a variety of medical systems. In the traditional medical systems, medical traditions partly cover other sectors of social life. In contrast to traditional health care system, the official health care system is based on Western science and technology. Gaddis employ different ways in case of sickness. Traditional medical knowledge is coded in to household cooking practices, home remedies; ill health prevention and health maintenance beliefs and routines. Like other rural parts of India, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…In most underdeveloped and in many developed countries, iron deficiency is the main cause of anemia among women and studies have shown that iron supplementation can prevent or correct the anemia [3, 28]. Our study supports the statement that low socio economic status, poor diet and nutritional deficiencies are associated with anemia [4, 14, 29]. …”
Section: Discussionsupporting
confidence: 87%
“…In most underdeveloped and in many developed countries, iron deficiency is the main cause of anemia among women and studies have shown that iron supplementation can prevent or correct the anemia [3, 28]. Our study supports the statement that low socio economic status, poor diet and nutritional deficiencies are associated with anemia [4, 14, 29]. …”
Section: Discussionsupporting
confidence: 87%